2022
DOI: 10.1159/000526720
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Effects of Blue Light Exposure on Skin: A Review of Published Literature

Abstract: The growing use of electronic devices and other artificial light sources in recent decades has changed the pattern of exposure to blue light (400–500 nm). Although some progress has been made in the study of the biological effects of blue light on the skin, many questions in this field remain unexplored. The aim of this article was to review the currently available evidence on the deleterious effects of blue light on the skin, as well as the methods and strategies designed to protect from the detrimental effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…Whether BL is harmful to skin cells is controversial [47]. The dose of BL used in our study was lower than that used in many reports.…”
Section: Discussionmentioning
confidence: 71%
“…Whether BL is harmful to skin cells is controversial [47]. The dose of BL used in our study was lower than that used in many reports.…”
Section: Discussionmentioning
confidence: 71%
“…This oxidation pathway could potentially contribute to photodamage in tissues that are directly exposed to visible light, such as skin and eyes. It has been reported that the blue light irradiation can lead to tissue aging and disorders, including the visible-light penetrating tissues [49][50][51][52][53][54] . The photodamage effects are suggested to result from elevated oxidative stress caused by blue light-induced ROS generation through endogenous photosensitizers 49,[55][56][57][58][59] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the blue light irradiation can lead to tissue aging and disorders, including the visible-light penetrating tissues [49][50][51][52][53][54] . The photodamage effects are suggested to result from elevated oxidative stress caused by blue light-induced ROS generation through endogenous photosensitizers 49,[55][56][57][58][59] . The photooxidation we report here may represent a hidden pathway within oxidative damage networks, contributing to overall protein damage in the skin and eyes.…”
Section: Discussionmentioning
confidence: 99%
“…A practical form of radiation treatment is the exposure of cultured mammalian cells to near-ultra-violet light (UVA, 315 nm < l < 400 nm) and visible light [ 62 ] in the presence of photosensitizers [ 63 ] at doses ranging from 0 to 5 J/cm 2 . Visible spectrum photosensitizers such as Ro 19 8022 are widely used for base oxidation; however, their efficiency in producing strand brakes is limited [ 64 ]. To produce measurable DNA double-strand breaks that are detectable by a γ- H2AX assay, CHO cells require pre-exposure with the catalyst benzo [a] pyrene (BaP) at concentrations ranging from 10 −9 mol/L to 10 −7 mol/L [ 65 ].…”
Section: Methods To Prepare and Analyze Reference Materialsmentioning
confidence: 99%